Foot spa to enhance tissue perfusion on diabetic foot ulcers - Amrie, Yunizar Nur Muhammad; Masithoh, Robiul Fitri; Kamal, Sodiq (Innovation in Health for Society, 2023)
Delayed wound healing is currently a concern in diabetic foot ulcer care. The problems occur due to ineffective blood flow to the wound, causing the leg muscles to feel stiff. Innovative approaches are needed to address this delay and accelerate healing. Therefore, this study aims to use a diabetic foot spa to increase tissue perfusion on the wound. The study uses a case study design involving one elderly patient living with a diabetic foot ulcer. Ethical clearance was obtained before the study began. A diabetic foot spa was implemented during the study. The research data uses descriptive research methods, interviews, and documentation. The findings show that diabetic foot spa improves tissue perfusion or blood flow to the feet within 5 days of use. The therapy also promoted blood flow to the wounds, relaxing and making the patient more comfortable. It is important to note that diabetic foot spacan be used in the community for patients living with diabetic foot ulcers. Keywords: Diabetic foot ulcers; innovation in health; community health; treatment; prevention